2013
DOI: 10.1111/1756-185x.12203
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal involvement in granulomatosis with polyangiitis and microscopic polyangiitis: histological features and outcome

Abstract: GI involvement in GPA and MPA is rare. Therapy directed at T cells might be an alternative treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Although gastrointestinal involvement in patients with granulomatosis with polyangiitis (GPA) or MPA is rare, 13 and at the autopsy of this case no vasculitis was found at the infarcted bowel segment, it would not be absurd to suspect gastrointestinal involvement since in the patient’s initial symptom was abdominal pain. Moreover, there was an iron deficiency anemia, and at the autopsy a hemorrhagic infarction band was found.…”
Section: Discussionmentioning
confidence: 79%
“…Although gastrointestinal involvement in patients with granulomatosis with polyangiitis (GPA) or MPA is rare, 13 and at the autopsy of this case no vasculitis was found at the infarcted bowel segment, it would not be absurd to suspect gastrointestinal involvement since in the patient’s initial symptom was abdominal pain. Moreover, there was an iron deficiency anemia, and at the autopsy a hemorrhagic infarction band was found.…”
Section: Discussionmentioning
confidence: 79%
“…6 – 8 Intestinal involvement has comparatively been described more frequently, often with mesenteric ischemia, ulceration, bleeding, or abdominal perforation. 3 , 9 , 10…”
Section: Discussionmentioning
confidence: 99%
“…Patients have higher Birmingham Vascular Assessment Scores and increased need for surgery with GI GPA, often because of acute abdomen or intractable bleeding. 9 , 10 One review found 54.5% mortality with GI involvement, and all cases reviewed required surgery. 13 Furthermore, GI GPA has been associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 12 18 Gastrointestinal symptoms were mainly acute abdominal pain, but other symptoms including nausea or vomiting, diarrhea, and gastrointestinal bleeding can be presenting symptoms. 14 , 19 21 In addition, gastric outlet obstruction, intussusception, and duodenal necrosis have been reported. 22 , 23 In our study, the most common primary vasculitis with UGI involvement was HSP (56.8%) and 76.4% of patients with primary vasculitis had gastrointestinal symptoms, abdominal pain being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal involvement of systemic vasculitis has been reported to be associated with severe complications and poor outcomes especially in patients with polyarteritis nodosa, microscopic angiitis, and granulomatosis with polyangiitis. 14 , 25 28 Therefore, accurate diagnosis and early treatment is important to avoid fatal outcomes, and endoscopic examination helps to define the site and extent of involvement and to assess prognosis. However, the diagnosis of vasculitis is difficult and endoscopic findings do not always correlate with presenting symptoms.…”
Section: Discussionmentioning
confidence: 99%